CodY Regulates Thiol Peroxidase Expression as Part of the Pneumococcal Defense Mechanism against H2O2 Stress - Hajaj, Barak; Yesilkaya, Hasan; Shafeeq, Sulman; Zhi, Xiangyun; Benisty, Rachel; Tchalah, Shiran; Kuipers, Oscar P.; Porat, Nurith (Frontiers in Cellular and Infection Microbiology, 2017)
Streptococcus pneumoniae is a facultative anaerobic pathogen. Although it maintains fermentative metabolism, during aerobic growth pneumococci produce high levels of H2O2, which can have adverse effects on cell viability and DNA, and influence pneumococcal interaction with its host. The pneumococcus is unusual in its dealing with toxic reactive oxygen species in that it neither has catalase nor the global regulators of peroxide stress resistance. Previously, we identified pneumococcal thiol peroxidase (TpxD) as the key enzyme for enzymatic removal of H2O2, and showed that TpxD synthesis is up-regulated upon exposure to H2O2. This study aimed to reveal the mechanism controlling TpxD expression under H2O2 stress. We hypothesize that H2O2 activates a transcription factor which in turn up-regulates tpxD expression. Microarray analysis revealed a pneumococcal global transcriptional response to H2O2. Mutation of tpxD abolished H2O2-mediated response to high H2O2 levels, signifying the need for an active TpxD under oxidative stress conditions. Bioinformatic tools, applied to search for a transcription factor modulating tpxD expression, pointed towards CodY as a potential candidate. Indeed, a putative 15-bp consensus CodY binding site was found in the proximal region of tpxD-coding sequence. Binding of CodY to this site was confirmed by EMSA, and genetic engineering techniques demonstrated that this site is essential for TpxD up-regulation under H2O2 stress. Furthermore, tpxD expression was reduced in a codY mutant. These data indicate that CodY is an activator of tpxD expression, triggering its up-regulation under H2O2 stress. In addition we show that H2O2 specifically oxidizes the 2 CodY cysteines. This oxidation may trigger a conformational change in CodY, resulting in enhanced binding to DNA. A schematic model illustrating the contribution of TpxD and CodY to pneumococcal global transcriptional response to H2O2 is proposed.